COMPETITIVENESS AND AUTHORITIES OF A COURT FOR SENDING THE CRIMINAL CASE TO A PROSECUTOR FOR ELIMINATING OBSTACLES IN ITS INVESTIGATION - D. V. Nametkin; A. O. Gryaznov (Russian Journal of Economics and Law)
Objective: on the basis of data doctrine and practice to show the level of development of the competition principle in the Russian criminal procedure legislation, as well as to identify the existing problems in the role of court in criminal proceedings concerning the powers to return the case to the Prosecutor, as well as features of the state Prosecutor’s role and the interaction between the investigator and the Prosecutor. Methods: the method of dialectics as general scientific method, which allows to show the historical development of the problem; analysis and synthesis – phenomena links; special-legislative and comparative-legislative methods – regularity of procedural institutions development. Results: analysis was based on the use of a large number of doctrinal sources and practices data that allowed us to draw the work from theoretical aspect to the level of law enforcement and to show the relevance of the existing problems. Scientific novelty: on the basis of empirical research it was clearly shown that the competitive principle is poorly developed in Russia during that stage of the criminal process, and thus results in conflicts and abuse of authority. Solutions to the problem are proposed. Objectivity of the study gives it a novelty, because the problem has not been studied in such a vast aspect. Practical value: the data can be used in both practice and in law-making and to improve the efficiency of public institutions, as well as to bring the work of these bodies to the qualitatively new level.